Genes, environment, and developmental timing: New insights from translational approaches to understand early origins of respiratory diseases. Issue 10 (13th August 2021) - Gutierrez, Maria J.; Perez, Geovanny F.; Gomez, Jose L.; Rodriguez‐Martinez, Carlos E.; Castro‐Rodriguez, Jose A.; Nino, Gustavo
Abstract: Over the past decade, "omics" approaches have advanced our understanding of the molecular programming of the airways in humans. Several studies have identified potential molecular mechanisms that contribute to early life epigenetic reprogramming, including DNA methylation, histone modifications, microRNAs, and the homeostasis of the respiratory mucosa (epithelial function and microbiota). Current evidence supports the notion that early infancy is characterized by heightened susceptibility to airway genetic reprogramming in response to the first exposures in life, some of which can have life‐long consequences. Here, we summarize and analyze the latest insights from studies that support a novel epigenetic paradigm centered on human maturational and developmental programs including three cardinal elements: genes, environment, and developmental timing. The combination of these factors is likely responsible for the functional trajectory of the respiratory system at the molecular, functional, and clinical levels.